Cognitive and linguistic factors affecting the selection of landscapes in the Corpus of Language and Nature. (14th July 2016) - Romero-Trillo, Jesús; Espigares, Tíscar
Abstract : The present paper attempts to establish the relationship between the linguistic and cultural background of speakers of different L1 and their description of nature. Specifically, our research has an interdisciplinary foundation and investigates the relationship between language, environmental background and the contemplation of natural landscapes in the Corpus of Language and Nature (henceforth CLAN). The CLAN project is a collection of over 4, 000 spoken descriptions of landscapes recorded online by 19 to 24-year-old university students from different parts of the world. The selection of the landscapes was based upon two variables: humid vs. non-humid landscapes and domesticated vs. non-domesticated landscapes. participants described 24 photographs combining the two variables, with six photographs per combination. The computer platform designed for the project presented the 24 photos in a random order and the students were instructed to freely choose the order of photos for their comments. The objective of the study is to analyze the participants' behavior in two aspects: the selection order of the photos and the duration of the contemplation and description of the photos. The results showed that the background environment and the number of languages spoken by the participants influenced the order of photograph selection and the duration of the descriptions. In sum, our article presents for the first time the relationship between the contemplation of landscapes and emotions from a linguistic perspective, and we believe that it can open research avenues to understand the cognitive processes in the linguistic and emotional evaluation of landscapes.